Insight Into the Wave Scattering Properties of the Solfatara Volcano, Campi Flegrei, Italy - Scala, Antonio; Serra, Marcello; Festa, Gaetano; Roux, Philippe (Frontiers in Earth Science, 2019)
In this study we inferred statistical properties related to the scatterers within a volcanic area, the Solfatara crater, located in the Campi Flegrei caldera, Southern Italy. We analyzed active seismic data recorded in a 3D geometry during the first RICEN experiment, held in September 2013. After extraction of seismic sections, we evaluated the coherent and incoherent intensities, averaging over sources and receivers sharing the same source-station distance. We thus computed the ratio between the two intensities over the surface waves, which is almost sensitive to the scattering mean free path in the area. We found that the intensity ratio exponentially decreases with distance, while the final plateau can be recognized only if the average is performed moving sources and receivers over the whole domain of investigation. We report that the scattering mean free path exhibits a small increase between 7.5 Hz and 10 Hz from 50 m to 60 m, and then it decreases down to about 10 m, at a frequency of 21.5 Hz. Since the scattering mean free path can be determined assuming a constant Rayleigh group velocity of 65 m/s, we modelled it as generated by a single scatterer of cylindrical shape in a homogeneous medium. We found that the average size of the scatterer is about 10 m, with a small increase of the Rayleigh wave velocity inside the scatterer. The scatterers are here interpreted as regions richer in water with respect to the background and eventually due to the condensed steam running below the investigated area.